The Influence of Leadership, Work Discipline, Work Motivation, and Job Satisfaction on Employee Performance Alfamart Megaregency Branch - Adiyati, Aisyah Puspita; Fa'uzobihi, Fa'uzobihi; Lesmana, Yanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to examine and analyze the influence of leadership, work discipline, work motivation, and job satisfaction on employee performance at Alfamart Megaregency Branch. The research sample includes all employees, totaling individuals. The data utilized in this study comprise primary data gathered through literature reviews and secondary data collected via questionnaires, interviews, and direct observation. The data were analyzed using multiple linear regression analysis, preceded by a series of tests such as validity tests, reliability tests, classical assumption tests, descriptive analysis, as well as significance tests (t-test and F-test). This research is expected to contribute significantly to the academic literature on human resource management, particularly in understanding the relationship between leadership, work discipline, motivation, and job satisfaction in enhancing employee performance.